An Atonement Problem for Contradictory Christology - Smith, Drew (TheoLogica, 2025)
Recently, Jc Beall has advanced a model of the incarnation according to which one can reconcile the apparently incompatible attributes attributed to Christ by taking them as true contradictions. In this paper, I argue that Contradictory Christology proves incompatible with a central class of atonement theories. I begin by expositing Beall’s model in contrast to two models operating upon the assumption of classical logic. Next, I demonstrate the incompatibility between Beall's theory and theories of the atonement on which Christ's suffering was a necessary condition of salvation. Finally, provide a brief survey of three prominent atonement theories, highlighting their endorsement of this principle.